Pengaruh Capital Adequacy Ratio, Debt To Equity Ratio, Rasio Biaya Operasional Pendapatan Operasional, Dan Loan To Deposit Ratio Terhadap Kinerja Keuangan Bank Umum Swasta Nasional Yang Go Public Di Bursa Efek Indonesia - Sochib Sochib (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2016)
This study has the objective to test empirically the influence of Capital Adequacy Ratio (CAR), Debt to Equity Ratio, Ratio of Operating Expenses to Operating Income (ROA), and Loan to Deposit Ratio (LDR) to the Financial Performance National Private Banks that Go Public in Indonesia stock exchange. Researchers used 13 samples of the banking industry listed in Indonesia Stock Exchange 2005-2009 period obtained by purposive sampling in order to obtain 65 observations. The hypothesis was tested using regression analysis which can be used for predicting the condition a few years after knowing the magnitude of the influence of the independent variables. Analysis of data to test regreasi and influence of independent variables on the dependent variable using SPSS. The results obtained in this study that the Capital Adequacy Ratio (CAR), Debt to Equity Ratio and Loan to Deposit Ratio (LDR) has no effect on the financial performance. While BOPO significant impact on the bank financial performance proxied Cash Flow Return on Assets (ROA). Expected results of this study can contribute in the development of Science in Accounting, in particular aspects of the factors that affect the financial performance of banks are proxied by Cash Flow Return on Assets.